2004
DOI: 10.1111/j.1523-1755.2004.00813.x
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous iron administration induces oxidation of serum albumin in hemodialysis patients

Abstract: The results of this study indicate that the HPLC analysis of serum albumin represents a potentially useful method for the quantitative and qualitative evaluation of oxidative stress in HD patients, and strongly suggest the possibility that oxidative stress, generated by IVIR, enhances the oxidation of albumin in those patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
1
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 42 publications
1
89
1
1
Order By: Relevance
“…We monitored the ratio of oxidized to unoxidized albumin as a marker for oxidative stress in the systemic circulation due to its simplicity, rapidity and sensitivity for evaluating oxidative stress in vivo because the oxidation of albumin accounts for almost all of the excess plasma protein oxidation in uremic patients. In fact, we previously demonstrated that intravenous iron induced oxidative stress in hemodialysis patients by this technique (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We monitored the ratio of oxidized to unoxidized albumin as a marker for oxidative stress in the systemic circulation due to its simplicity, rapidity and sensitivity for evaluating oxidative stress in vivo because the oxidation of albumin accounts for almost all of the excess plasma protein oxidation in uremic patients. In fact, we previously demonstrated that intravenous iron induced oxidative stress in hemodialysis patients by this technique (16).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress was evaluated by monitoring oxidized serum albumin levels, a sensitive marker for protein oxidation in the systemic circulation (16). Furthermore, we investigated the effect of IS on ROS production in endothelial cells to verify the mechanism of the antioxidant activity of AST-120 in CRF.…”
Section: Introductionmentioning
confidence: 99%
“…27 Thiol concentrations in plasma were measured by means of the Ellman's method. 28 Reaction mixtures were prepared by adding 20 ml of plasma to 100 ml of 5 mM 5, 5 0 -dithiobis (2-nitrobenzoic acid) in 100 mM potassium phosphate (pH 7.0).…”
Section: Determination Of Thiol Contentmentioning
confidence: 99%
“…27 Frozen plasma samples obtained from healthy volunteers and heterozygotic FAP ATTR V30M patients were thawed, and then 5 ml aliquots were analyzed with a Shodex Asahipak ES-502N column (Showa Denko, Tokyo, Japan). The values of the reduced form (HMA) and the oxidized form (HNA) of plasma albumin were estimated from HPLC chromatograms by dividing the area of each fraction by the total area corresponding to albumin.…”
Section: Chromatography Of Oxidized Albuminmentioning
confidence: 99%
“…The aim of this study was to examine the possible antioxidant and free radical-scavenging properties of olmesartan in in vitro studies. We also evaluated the effect of once daily administration of 40 mg of olmesartan on BP and on oxidized serum albumin, a marker of protein oxidation, in HD patients (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%